Pengaruh Rasio Likuiditas, Solvabilitas dan Profitabilitas Terhadap Harga Saham Pada Perusahaan Indeks LQ45 - Auliffi Ermian Challen; Elmanizar Elmanizar; Erina Amarvia Yunazar (Lembaga Penelitian Universitas YARSI, 2023)
This study aims to analyze the effect of liquidity ratios, solvency ratios, and profitability ratios on stock prices. This study uses a sample of companies included in the LQ45 index listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The analysis technique used is multiple linear regression analysis. Testing the hypothesis used is a partial statistical test (t-test) with the test results showing that only the solvency ratio variable has a negative effect on stock prices and the profitability ratio has a positive effect on stock prices. While the variable liquidity ratio has no effect on stock prices.